2019
DOI: 10.1161/jaha.119.012790
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Placental Growth Factor Concentrations Are Elevated Well in Advance of Type 2 Diabetes Mellitus Onset: Prospective Data From the WHS

Abstract: BackgroundPathologic angiogenesis is a hallmark of type 2 diabetes mellitus (T2DM) microvascular complications and may modulate adipogenesis and precede the onset of clinical diabetes mellitus; however, longitudinal data are unavailable. Placental growth factor is a potent proangiogenic factor that stimulates the formation of mature and durable vessels but is understudied in human diseases.Methods and ResultsWe conducted a prospective case‐cohort study of baseline placental growth factor and incident T2DM with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…51 In type 2 diabetic mellitus (T2DM), plasma PlGF concentrations are elevated before pathologic angiogenesis occurrence, suggesting that PlGF may serve as a potential biomarker for diagnosis of microvascular complication in T2DM patients. 52 Vitreous levels of PlGF signi cantly (p < 0.05) correlated with pathological angiogenesis and VEGF levels in diabetic patients with active PDR, and its receptor VEGFR1 (or FLT1) were detected in the ECs of proliferative neovasculature. 53 Another study also reported that vitreous PlGF levels are signi cantly higher in diabetic patients with DR than without DR. 54 These studies with clinical samples indicated that PlGF/VEGFR1 signaling is involved in the retinal microvascular complications both NPDR and PDR.…”
Section: Discussionmentioning
confidence: 92%
“…51 In type 2 diabetic mellitus (T2DM), plasma PlGF concentrations are elevated before pathologic angiogenesis occurrence, suggesting that PlGF may serve as a potential biomarker for diagnosis of microvascular complication in T2DM patients. 52 Vitreous levels of PlGF signi cantly (p < 0.05) correlated with pathological angiogenesis and VEGF levels in diabetic patients with active PDR, and its receptor VEGFR1 (or FLT1) were detected in the ECs of proliferative neovasculature. 53 Another study also reported that vitreous PlGF levels are signi cantly higher in diabetic patients with DR than without DR. 54 These studies with clinical samples indicated that PlGF/VEGFR1 signaling is involved in the retinal microvascular complications both NPDR and PDR.…”
Section: Discussionmentioning
confidence: 92%
“…PlGF expression is modulated by hyperglycaemia in endothelial cells. Elevated circulating PlGF has recently been identified in insulin resistance, metabolic syndrome, vascular inflammation and is an independent marker of the future development of type-II diabetes [19][20][21][22] . To determine whether hyperglycaemia upregulates the expression of PlGF, we incubated confluent primary human endothelial cells in medium containing 30 mM d-glucose for 24 h and measured the level of PlGF released into the medium by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…PlGF mRNA is expressed in white adipose tissue 53 , and PlGF (−/−) knock-out mice have a lower body weight and fat content than wild-type mice and a lower fat content when maintained on a high-fat diet 54 . Whether this is due to endothelial or adipocyte PlGF production was not fully established, but it suggests that in addition to increased risk of type II diabetes 21 and CVD 19,[23][24][25] , up-regulation of PlGF in insulin resistance/hyperglycaemia and the metabolic syndrome may also accelerate the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…55 Limited clinical data shows increased PlGF in obese non-pregnant adults and children with the metabolic syndrome and diabetes. [56][57][58] While studies are small and data sometimes conflict, a positive association between elevated PlGF and GDM has been established. [59][60][61] A recent literature review concludes that although large-scale research is missing, most studies agree with this observation.…”
Section: Placental Biomarkersmentioning
confidence: 99%